China-Pakistan Educational and Cultural Cooperation under the Belt and Road Initiative - Dr. Muhammad Asif Noor (Pacific International Journal, 2023)
Implementing the Belt and Road Initiative has increased the focus on cultural and educational cooperation between Pakistan and China. As the China-Pakistan Economic Corridor (CPEC) is a key component of the initiative, both countries have sought to diversify their bilateral relationship by promoting cultural and educational exchange. China has sponsored various institutes in Pakistan to teach Chinese Confucianism, language, and culture. Despite Pakistan's openness to interacting with foreign cultures, certain cultural pockets within the country, specifically in Baluchistan and Khyber Pakhtunkhwa, may present challenges in terms of cultural exchange. The ongoing global pandemic has temporarily hindered the implementation of mutual understanding through cultural and educational exchange, but both nations remain committed to resuming these activities in the future. Higher education and cultural tourism have been identified as areas of potential cooperation that can enhance not only public diplomacy but also foster people-to-people contact. The China-Pakistan Economic Corridor, as a flagship project of the Belt and Road Initiative, provides a valuable opportunity to develop these areas of cooperation further.